2016
DOI: 10.1101/073387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An efficient electroporation protocol for the genetic modification of mammalian cells

Abstract: Genetic modification of cell lines and primary cells is an expensive and cumbersome approach, often involving the use of viral vectors. Electroporation using square-wave generating devices, like Lonza's Nucleofector, is a widely used option, but the costs associated with the acquisition of electroporation kits and the transient transgene expression might hamper the utility of this methodology. In the present work, we show that our in-house developed buffers, termed Chicabuffers, can be efficiently used to elec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…pH 6.5). While complexing, cells were washed 2× in icecold PBS at 100 × g. Cells were resuspended in ice-cold 100 μl final volume Chikabuffer 1 52 and nucleofected in a 1D-nucleofector (program X-001). Immediately following nucleofection, cells were transferred to pre-warmed/equilibrated 10% serum RPMI for indicated time points.…”
Section: Methodsmentioning
confidence: 99%
“…pH 6.5). While complexing, cells were washed 2× in icecold PBS at 100 × g. Cells were resuspended in ice-cold 100 μl final volume Chikabuffer 1 52 and nucleofected in a 1D-nucleofector (program X-001). Immediately following nucleofection, cells were transferred to pre-warmed/equilibrated 10% serum RPMI for indicated time points.…”
Section: Methodsmentioning
confidence: 99%
“…2d to g insets). This electric field condition is below literature reported, well-recognized electroporation field strength (~2000 V/cm for > 80% cell viability) for HeLa cells [37][38][39] . Meanwhile, our experimental study showed that our voltage condition at 400 V can achieve more than 90% cell viability (Fig.…”
Section: Working Principles Of Multi-directional Electric Field Scanning Enabled 3d Transfectionmentioning
confidence: 54%
“…The Lonza Nucleofector II Electroporator performs effective genetic alteration of T cells using certain electric parameters and electroporation buffers (39). The electroporation of human T cells has been reported to be associated with ~40-60% of gene expression and 80% of cell viability (40). One of the limitations of electroporation is the low transfection efficiency and redundant cell damage (41).…”
Section: Non-viral Delivery Methodsmentioning
confidence: 99%